CD4+ T Cell Response to Factor VIII in Hemophilia A, Acquired Hemophilia, and Healthy Subjects - Reding, M.T.; Wu, H.; Krampf, M.; Okita, D.K.; Diethelm-Okita, B.M.; Key, N.S.; Conti-Fine, B.M. (Thrombosis and Haemostasis, 1999)
In spite of the significant advances in the treatment of hemophilia over the last 30 years, the development of antibodies that neutralize the procoagulant activity of factor VIII (factor VIII inhibitors) remains a serious complication of treatment with factor VIII products. Recent prospective studies of previously untreated patients with severe hemophilia have reported the incidence of inhibitor development to be approximately 20% to 25%.1-11 Factor VIII inhibitors may also develop in individuals without congenital factor VIII deficiency. Acquired autoimmune hemophilia occurs with an incidence of 0.2 to 1.0 per 1,000,000 per year in the general population.12,13 In both congenital and acquired hemophilia, anti-factor VIII antibody inhibitors are significant contributors to the morbidity and mortality of those affected. As such, these cases present difficult therapeutic challenges.Much work over the last decade has focused on defining the epitopes on factor VIII to which inhibitor antibodies bind. While this work has clarified some of the mechanisms by which inhibitors neutralize the procoagulant function of factor VIII, our knowledge of the factor VIII-specific CD4+ T helper cells, whose activation is crucial for the synthesis of factor VIII inhibitors, remains quite limited. This review will, first, discuss how a better understanding of the cellular mechanisms involved in the immune response to factor VIII may lead to improved methods of long-term inhibitor suppression and, perhaps, even prevention of inhibitor development. Lastly, this review will describe the work in our laboratory that has begun to characterize the CD4+ T cell response to factor VIII in patients with hemophilia and in normal subjects.